Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2017)
Table of Content New York Roundtable, Nikki Columbus, Bice Curiger, Hal Foster, Michelle Kuo Hrag Vartanian Berlin Roundtable, Jacqueline Burckhardt, Bice Curiger, Diedrich Diederichsen, Jörg Heiser, Olaf Nicola, Susanne Pfeffer, Mark Welzel, Steffen Zillig From the Archive Statements from Editors, Designers, Translators, Curators Marlene Dumas The Saturated Image by Tamar Garb Jordan Wolfson The Bully Pulpit by Andrew Russeth Katharina Fritsch Atmosphere Becomes Form by Jacqueline Burckhardt Maurizio Cattelan Years without Art: Maurizio Cattelan and the End of Labour by Massimiliano Gioni Nairy Baghramian Occupational Hazard by Caoimhín Mac Giolla Léith Pipilotti Rist Thoughts Grow in Me Like a Forest by Juliana Engberg Marilyn Minter Marilyn Minter’s Bad Bitch Feminism by Nancy Spector Nicolas Party The First Form of Art by Ali Subotnick Katharina Grosse Post-Essential Abstraction by Barry Schwabsky Jean-Luc Mylayne Exchanging Views by Matthew S. Witkovsky Artists’s Statements Vito Acconci is Dead, Cumulus from New York by Tom Eccles We Will Rise from the Ashes, Cumulus from Detroit by Taylor Renee Aldridge Interinanimative Flesh: On Narcissister’s Muscle Memory by Tavia Nyong’O Floored in Wonder, Balkon by Marina Warner
﻿The collaborative strength of Parkett unfolds with artists and writers, with retrospective and future views — one last time. Parkett’s closing print issue is a double one — one volume is a traditional issue, this time with ten new artist collaborations, while the other consists of recollections and tributes. Going forward, Parkett volumes and editions will remain fully documented on the website and available via the Zurich and New York offices. Furthermore, all volumes including 1500 texts are currently being digitized and will become accessible online. New, expanded Parkett exhibitions in various museums are in preparation as well, which will further explore the publication’s singular approach as a thirty-three-year time capsule and archive. The double issue features collaborations with Nairy Baghramian, Maurizio Cattelan, Marlene Dumas, Katharina Fritsch, Katharina Grosse, Marilyn Minter, Jean-Luc Mylayne, Nicolas Party, Pipilotti Rist, and Jordan Wolfson. Each artist has created as usual a special limited edition. Collaboration texts are by Caoimhín Mac Giolla Léith (on Nairy Baghramian), Massimiliano Gioni (on Maurizio Cattelan), Tamar Garb (on Marlene Dumas), Jacqueline Burckhardt (on Katharina Fritsch), Barry Schwabsky (on Katharina Gorsse), Nancy Spector (on Marilyn Minter), Matthew S. Witkovsky (on Jean-Luc Mylayne), Ali Subotnick (on Nicolas Party), Juliana Engberg (on Pipilotti Rist), and Andrew Russeth (on Jordan Wolfson). (editorial by publisher)
boek
Keywords: Minter, Marilyn; Baghramian, Nairy; Rist, Pipilotti; Cattelan, Maurizio; Fritsch, Katharina; Grosse, Katharina; Dumas, Marlene; Party, Nicolas; Mylayne, Jean-Luc; Wolfson, Jordan